Genistein and estradiol have common and specific impacts on the sea bass (Dicentrarchus labrax) skin-scale barrier. Issue 195 (December 2019) - Pinto, Patricia I.S.; Andrade, André R.; Moreira, Catarina; Zapater, Cinta; Thorne, Michael A.S.; Santos, Soraia; Estêvão, M. Dulce; Gomez, Ana; Canario, Adelino V.M.; Power, Deborah M.
Highlights: Genistein transactivated the three fish nuclear estrogen receptors. 254 estrogen (E2)- and/or genistein (Gen)-responsive genes were identified in the scales transcriptome. 65 genes were specifically responsive to E2, 106 to Gen and 83 to both compounds. Innate immunity-related genes were affected by both compounds. E2 and Gen specifically affected protein/matrix turnover and sterol biosynthesis/regeneration, respectively. Abstract: Teleost fish scales play important roles in animal protection and homeostasis. They can be targeted by endogenous estrogens and by environmental estrogenic endocrine disruptors. The phytoestrogen genistein is ubiquitous in the environment and in aquaculture feeds and is a disruptor of estrogenic processes in vertebrates. To test genistein disrupting actions in teleost fish we used a minimally invasive approach by analysing scales plucked from the skin of sea bass ( Dicentrarchus labrax ). Genistein transactivated all three fish nuclear estrogen receptors and was most potent with the Esr2, had the highest efficacy with Esr1, but reached, in all cases, transactivation levels lower than those of estradiol. RNA-seq revealed 254 responsive genes in the sea bass scales transcriptome with an FDR < 0.05 and more than 2-fold change in expression, 1 or 5 days after acute exposure to estradiol or to genistein. 65 genes were specifically responsive to estradiol and 106 by genistein while 83 genes were responsive to both compounds. Estradiol specifically regulated genes of protein/matrix turnover and genistein affected sterol biosynthesis and regeneration, while innate immune responses were affected by both compounds. This comprehensive study revealed the impact on the fish scale transcriptome of estradiol and genistein, providing a solid background to further develop fish scales as a practical screening tool for endocrine disrupting chemicals in teleosts.